Stabilization of optically coupled lasers with periodic pumping - Torres, P.J. (Нелінійні коливання, 2011)
We study a periodically forced system modeling the synchronization of two optically coupled lasers pumped by an alternating current. A necessary and sufficient condition for existence of a periodic solution is given, as well as a sufficient condition for uniqueness and asymptotic stability.